Massive Hemoptysis: A Meta-Analysis of Urgent Interventional Approaches - Bambang Rojullun Taufik; Russilawati; Dewi Wahyu Fitrina (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Massive hemoptysis is a life-threatening medical emergency requiring immediate intervention. This meta-analysis evaluated the efficacy and safety of urgent interventional approaches for managing massive hemoptysis. Methods: A systematic search of electronic databases (PubMed, Embase, Scopus) was conducted from January 2013 to February 2024. Studies comparing different urgent interventional approaches (bronchial artery embolization [BAE], bronchoscopic interventions, surgery) in adults with massive hemoptysis were included. The primary outcome was treatment success (cessation of bleeding). Secondary outcomes included mortality, complications, and length of hospital stay. Results: Nine studies (n=1145 patients) were included. BAE was the most common intervention (7 studies), followed by bronchoscopic interventions (4 studies) and surgery (3 studies). Pooled analysis showed that BAE had a higher success rate compared to bronchoscopic interventions (OR 2.15, 95% CI 1.32-3.51, p=0.002) and surgery (OR 1.88, 95% CI 1.15-3.08, p=0.01). BAE was associated with a lower mortality rate compared to surgery (OR 0.43, 95% CI 0.21-0.88, p=0.02) but not bronchoscopic interventions (OR 0.78, 95% CI 0.45-1.35, p=0.37). Complication rates were similar across all interventions. Conclusion: BAE appears to be the most effective urgent interventional approach for massive hemoptysis, with a higher success rate and lower mortality compared to surgery. Bronchoscopic interventions may be considered in selected cases. Further research is needed to compare different BAE techniques and optimize patient selection.